Considering Exposure Assessment in Epidemiological Studies of Chronic Health in Military Populations - Hall, Amy L.; MacLean, Mary Beth; VanTil, Linda; McBride, David Iain; Glass, Deborah C. (Frontiers in Public Health, 2020)
Exposure assessment is an important factor in all epidemiological research seeking to identify, evaluate, and control health risks. In the military and veteran context, population health research to explore exposure-response links is complicated by the wide variety of environments and hazards encountered during active service, long latency periods, and a lack of information on exposures in potentially vulnerable subgroups. This paper summarizes some key considerations for exposure assessment in long-term health studies of military populations, including the identification of hazards related to military service, characterization of potentially exposed groups, exposure data collection, and assignment of exposures to estimate health risks. Opportunities and future directions for exposure assessment in this field are also discussed.